MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VC SD NEGERI 164 PEKANBARU DENGAN MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER (NHT) - Rosita L. Tobing (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The problem of classroom action research is the low learning outcomes of VC grade 164 students in Pekanbaru. This study aims to improve social studies learning outcomes of VC grade 164 students in Pekanbaru by applying the cooperative method of numbered heads together (NHT). The results of the research and class actions of the Social Studies Course conducted at the VC class SDN 164 Pekanbaru students concluded; Learning outcomes in the first cycle have increased compared to conventional learning. Pre-cycle learning outcomes are an average of 50.25 or sufficient categories; in cycle I, learning outcomes reached an average of 71.75 or in the Good category; in cycle II it increased again by 80.25 or in the Good category; Prasiklus classical completeness is 10 students (25.00%.); the first cycle is 27 students (67.50%); and in the second cycle were 38 students (95.00%). Students who have not been completed are remedial. Observers observed that VC grade 164 students at Pekanbaru Pekanbaru seemed to understand the Numbered Heads Together (NHT) Cooperative Method. They learn and understand shared material in heterogeneous groups of 4-5 students. Based on the results of improved learning studies, the application of the cooperative method of numbered heads together (NHT) succeeded in correcting the problem of the low social studies learning outcomes in VC Class SDN 164 Pekanbaru 2017/2018 Academic Year.